2021
DOI: 10.1111/jfb.14932
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary records of the rare and critically endangered angular rough shark, Oxynotus centrina (Linnaeus, 1758), from the eastern Adriatic Sea

Abstract: The angular rough shark, Oxynotus centrina (Linnaeus, 1758), is a poorly known and rare bathydemersal shark inhabiting continental shelves and upper slopes with a significant lack of data and rarely published records in the Adriatic Sea in this century. In this paper, we present 20 new occurrences recorded from May 2015 to September 2021, of which 19 are in Croatian and one in Montenegrin territorial waters. Records of juveniles, subadults and adults are reported. Higher number of records off the Kornati archi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…2). To the best of the authors' knowledge, the smallest individual recorded to date from the Adriatic Sea was 300 mm in total length and weighed 430 g (in Gajić et al, 2021). However, Cugini and De Maddalena (2003) recorded a pregnant female in the Adriatic Sea and suggested that this species is among the rarest sharks in the surveyed area.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…2). To the best of the authors' knowledge, the smallest individual recorded to date from the Adriatic Sea was 300 mm in total length and weighed 430 g (in Gajić et al, 2021). However, Cugini and De Maddalena (2003) recorded a pregnant female in the Adriatic Sea and suggested that this species is among the rarest sharks in the surveyed area.…”
Section: Resultsmentioning
confidence: 97%
“…It is well known that it does not have any economic value and therefore it is not landed, which could be a possible reason for the rarity of species records records from the eastern Adriatic, suggesting that the species could be less rare than is commonly thought. Such an increase in the number of records might be a result of the more intense usage of citizen science in recent years, as half of the records provided in Gajić et al (2021) come either from direct reports from fishers or from social networks. On the other hand, studies that indicate a very narrow feeding niche, characterized by the consumption of elasmobranch eggs (Guallart et al, 2015;Mulas et al, 2021) could also explain the rarity of this species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxynotus centrina (Linnaeus, 1758) is critically endangered in the Mediterranean Sea, according to the IUCN [12]. Records show a distribution along the entire Croatian coast, with a particular aggregation near the central Adriatic Sea, where many new individuals have been found in recent years [48]. Almost all records are from the last twenty years when the sharks were caught by trawling in water depths between 40 and 125 m. It is included in the Croatian list of strictly protected species (Regulation on strictly protected species, Annex 1, 2013) [83].…”
Section: Squaliformesmentioning
confidence: 99%